Implementasi Akad Mudharabah, Musyarakah dan Salam Pada Petani Ikan di Provinsi Jambi - Amrizal; Khoirul Mu’as; Iwan Setiadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The practice of Sharia Economic transactions is a concept that meets the values ​​of justice, the togetherness of Ukhwatun Hasanah values ​​such as profit sharing contracts in the form of Mudarabah and Musyarakah contracts including buying and selling contracts with the salam contract scheme. The research objective is to analyze the application of the Mudarabah agreement to fish cultivation in Jambi Province. The research object is a catfish farming group, the research design uses qualitative descriptive research with 20 informants from the head of the catfish farming group in Jambi province. The data collection technique is by conducting in-depth interviews, while the research results are analyzed using content analysis. The research results prove that the analysis of the implementation of the first sharia contract, the implementation of the mudarabah contract, proved that there were several capital owners and managers in implementing the terms of the contract that were not in accordance with the terms of the mudarabah contract. Second, Implementation of the musyarakah agreement betweencatfish cultivation partners have been carried out in accordance with the terms of the Musyarakah agreement. If there are profits, they are shared according to the agreement and if there are losses, they are equally borne by the capital owner. Third, the implementation of the greeting contract is in accordance with the pillars of the greeting contract. Implementation of a sale and purchase agreement with greetings can provide benefits to both parties. The buyer can buy fish products with definite quality and price in accordance with the agreement. On the other hand, the farmers greatly benefit from the funder's tone for raising fish and the results can be sold at a price. profitable prices, so that catfish farms can be free from the grip of loan sharks.